Testing Wallace's intuition: water type, reproductive isolation and divergence in an Amazonian fish - Pires, Tiago H.S.; Borghezan, Elio A.; Machado, Valéria Nogueira; Powell, Daniel L.; Röpke, Cristhiana Paula; Oliveira, Claudio; Zuanon, Jansen; Farias, Izeni P. (Journal of Evolutionary Biology, 2018)
Alfred Russel Wallace proposed classifying Amazon rivers based on their colour and clarity: white, black and clear water. Wallace also proposed that black waters could mediate diversification and yield distinct fish species. Here, we bring evidence of speciation mediated by water type in the sailfin tetra (Crenuchus spilurus), a fish whose range encompasses rivers of very distinct hydrochemical conditions. Distribution of the two main lineages concords with Wallace's water types: one restricted to the acidic and nutrient-poor waters of the Negro River (herein Rio Negro lineage) and a second widespread throughout the remaining of the species’ distribution (herein Amazonas lineage). These lineages occur over a very broad geographical range, suggesting that despite occurring in regions separated by thousands of kilometres, individuals of the distinct lineages fail to occupy each other's habitats, hundreds of metres apart and not separated by physical barrier. Reproductive isolation was assessed in isolated pairs exposed to black-water conditions. All pairs with at least one individual of the lineage not native to black waters showed significantly lower spawning success, suggesting that the water type affected the fitness and contributed to reproductive isolation. Our results endorse Wallace's intuition and highlight the importance of ecological factors in shaping diversity of the Amazon fish fauna. © 2018 European Society For Evolutionary Biology. Journal of Evolutionary Biology © 2018 European Society For Evolutionary Biology
Keywords: Divergence; Fish; Fitness; Freshwater Environment; Reproductive Isolation; Selection; Sexual Selection; Spatial Distribution; Spawning; Speciation (biology); Testing Method; Amazonas; Rio Negro [south America]; Crenuchus Spilurus; Dna, Mitochondrial; Water; Adaptation; Animals; Characiformes; Evolution; Genetic Variation; Genetics; Physiology; Species Differentiation; Adaptation, Physiological; Animal; Biological Evolution; Characiformes; Dna, Mitochondrial; Genetic Speciation; Genetic Variation; Water